Good response with durvalumab after chemoradiotherapy for epidermal growth factor receptor exon 20 insertion adenocarcinoma: A case report. (2020) - Matsuura, Shun; Morikawa, Keisuke; Ito, Yutaro; Kagoo, Namio; Kubota, Tsutomu; Ichijo, Koshiro; Mochizuki, Eisuke; Uehara, Masahiro; Harada, Masanori; Tsukui, Masaru; Koshimizu, Naoki
Abstract: Epidermal growth factor receptor (EGFR) exon 20 insertion is not associated with sensitivity to EGFR tyrosine kinase inhibitors and chemotherapy. Here, we report the case of a 41-year-old man who presented a right lower lobe nodule and mediastinal lymph node enlargement diagnosed as EGFR exon 20 insertion adenocarcinoma with high-expression programmed cell death ligand 1 (PD-L1). He showed stable disease to chemoradiation treatment at the primary tumor site. However, durvalumab treatment has good response. Non-small cell lung cancer with EGFR exon 20 insertion and high PD-L1 expression may be treated with immunotherapy exposure.